Features of the rare pathogen Meyerozyma guilliermondii strain SO and comprehensive in silico analyses of its adherence-contributing virulence factor agglutinin-like sequences - Si, Jie Lim; Muhd Noor, Noor Dina; Sabri, Suriana; Mohamad Ali, Mohd Shukuri; Salleh, Abu Bakar; Oslan, Siti Nurbaya (Taylor and Francis Group, 2023)
Meyerozyma guilliermondii is a rare yeast pathogen contributing to the deadly invasive candidiasis. M. guilliermondii strain SO, as a promising protein expression host, showed 99% proteome similarity with the clinically isolated ATCC 6260 (type strain) in a recent comparative genomic analysis. However, their in vitro virulence features and in vivo pathogenicity were uncharacterized. This study aimed to characterize the in vitro and in vivo pathogenicity of M. guilliermondii strain SO and analyze its Als proteins (MgAls) via comprehensive bioinformatics approaches. M. guilliermondii strain SO showed lower and higher sensitivity towards β-mercaptoethanol and lithium, respectively than the avirulent S. cerevisiae but exhibited the same tolerance towards cell wall-perturbing Congo Red with C. albicans. With 7.5× higher biofilm mass, M. guilliermondii strain SO also demonstrated 75% higher mortality rate in the zebrafish embryos with a thicker biofilm layer on the chorion compared to the avirulent S. cerevisiae. Being one of the most important Candida adhesins, sequence and structural analyses of four statistically identified MgAls showed that MgAls1056 was predicted to exhibit the most conserved amyloid-forming regions, tandem repeat domain and peptide binding cavity (PBC) compared to C. albicans Als3. Favoured from the predicted largest ligand binding site and druggable pockets, it showed the highest affinity towards hepta-threonine. Non-PBC druggable pockets in the most potent virulence contributing MgAls1056 provide new insights into developing antifungal drugs targeting non-albicans Candida spp. Virtual screening of available synthetic or natural bioactive compounds and MgAls1056 deletion from the fungal genome should be further performed and validated experimentally.